O professor no espelho: refletindo sobre a leitura de um relatório de estágio na graduação em letras - FAIRCHILD, Thomas Massao (Universidade Federal do Pará, 2018)
In this paper we defend that one of the main drawbacks in Portuguese first language teaching in Brazil is the teachers’ difficulty to sustain a specific discourse about their object of expertise, which in turn puts their professional status at stake. In order to revert this, we have been studying how a “professional teacher’s discourse” comes into being by analyzing pieces written by undergraduate students in Languages and Literature. We present here an analysis of an internship report based on the concept of “image” such as proposed by Pêcheux (1969). We discuss particularly writing procedures that favor the subject’s evading her own experience more than using it to build new knowledge. In this case, instead of using theoretical instruments, the subject clings to explanations that stand beside her object of analysis, moved by the need to conceal an image she sustains of herself as a teacher. The result is a construction that can hardly push towards any educational improvement, but rather preserves the layman character of her discourse.